Agritourism and the adaptive re-use of farm buildings in New Zealand - Mackay Michael; Nelson Tracy; Perkins Harvey C. (Open Agriculture, 2019)
This paper reports findings from a study of the adaptive re-purposing of farm buildings for a wide array of agritourism activities. The research is being conducted in New Zealand where the international visitor sector is thriving. In response, an increasing number of farmers are attempting to boost their farm incomes by adding tourism ventures to their business portfolios. In doing so, many of them are using and preserving rural cultural heritage, particularly old agricultural and other rural buildings, while also diversifying farm activity. This element of agritourism therefore has an important role in the protection and adaptive re-use of farm buildings, farm landscape change, and the creation of new value and values in the countryside. In the cases we have studied, this entrepreneurial activity is largely farmer-driven and undertaken with some, but limited, financial support from central and local government. In considering the policy implications of our work, we call for the provision of advisory services to facilitate and enable New Zealand farmers to create profitable and sustainable high-quality tourism services that simultaneously preserve farm buildings.